Thick Europe, ontological security and parochial Europe: the re-emergence of far-right extremism and terrorism after the refugee crisis of 2015. Issue 1 (1st January 2022) - Kaunert, Christian; de Deus Pereira, Joana; Edwards, Mike
ABSTRACT: This article examines the re-emergence of far-right extremism and terrorism as the adversary of European integration. The European Union (EU) becoming a grievance factor for far-right extremism and terror is qualitatively new. This article examines the emergence of this new actor in line with the changing four faces of the EU presented in this special issue, namely thin, thick, parochial and global. Paradoxically, the core argument of this article is that moves towards thick Europe have contributed to this development by way of addressing core fears in Europe after the migration/refugee crisis in 2015. The chronological discourse of the construction of the EU's identity has showed that since 2014, there has been a major shift regarding Europeans' fears and anxieties. (In)security linked to the migration/refugee crisis has been widening the market for security, despite the contrasting fact that Europe has been thriving for the longest peace period since WWII. This article analyses the impacts of the refugee crisis on the mutation of the European perception of threats. It uses the concept of ontological security to understand how the anxiety and fear caused by the refugee crisis led to the shaping of the European self-identity crisis.